Determinants of Trust in Cash Waqf Linked Sukuk (CWLS) Stakeholder Institutions: Evidence from A Survey of Indonesian Muslims - Anggraini, Ika Khusnia; Widiyanti, Dwi Retno; Nusantara, Wisam Zuhdi Surya; Rizaldi, Muhammad (Jurnal Penelitian Inovatif, 2024)
This study aims to identify and analyze the influence of the implementation of Good Corporate Governance (GCG), which consists of indicators of transparency, accountability, responsibility, independence, and fairness in three CWLS stakeholder institutions, namely Bank Syariah Indonesia (BSI), Badan Wakaf Indonesia (BWI), and the Indonesian Ministry of Finance. This research falls under quantitative research because the approach used for research proposals, processes, hypotheses, fieldwork, data analysis, and data conclusions up to the writing uses aspects of measurement, calculation, formulas, and certainty of numerical data. The research subjects were Muslim communities who had become CWLS investors and those who had the potential to become investors. In this study, the population and sample were all Muslim community investors and prospective CWLS investors, which collected 261 people. Data were analyzed using multiple linear regression formula. The results of the study show that partially the implementation of GCG in the three CWLS stakeholder institutions, namely BSI, BWI, and MoF, has a significant effect on the level of public trust. Simultaneously, these three institutions also significantly affect the level of public trust in the CWLS management institution.